Simulation investigation of a Ka-band phase-locked klystron-type coaxial relativistic Cherenkov generator - Yunxiao Zhou; Jinchuan Ju; Wei Zhang; Dian Zhang; Ying Li; Tengfang Wang; Fugui Zhou; Zhuang Yu; Hongtao Yao; Jun Zhang (AIP Advances)
To achieve coherent power combination of Ka-band high-power microwave (HPM), a phase-locked klystron-type coaxial relativistic Cherenkov generator (PKC-RCG), which combines the advantageous characteristics of weak dimensional sensitivity of RCG and low input power ratio of relativistic triaxial klystron amplifier (TKA), is proposed and investigated in this paper. The PKC-RCG is composed of two parts: a pre-modulation region adapted from TKA and an energy exchange region adapted from RCG. The pre-modulation region is used for initial speed modulation of intense relativistic electron beams (IREB), ensuring that the output frequency is consistent with the input frequency. The energy exchange region is used for deep clustering of the IREB and achieving efficient beam–wave energy conversion. Phase locking of the output HPM is accomplished through phase delivery of the modulated IREB. Specially designed reflectors and cascaded single-gap bunching cavities with active suppression of asymmetric TM mode are employed in the pre-modulation region to suppress energy coupling and achieve a lower input power ratio. Disk-loaded slow-wave structure with smooth inner conductor is employed in the energy exchange region to further decrease the dimensional sensitivity of RCG. By the proposed Ka-band PKC-RCG, an HPM with a power of 550 MW and a frequency of 29.0 GHz is obtained with ohmic loss being taken into account. Moreover, the input power ratio and phase-locking bandwidth of the proposed Ka-band PKC-RCG are −51.4 dB and 30 MHz, respectively.